Nutrition security, constraints, and agro-diversification strategies of neglected and underutilized crops to fight global hidden hunger - Ali, Akib; Bhattacharjee, Bijoya (Frontiers in Nutrition, 2023)
Introduction: Neglected and Underutilized Crop Species (NUCS) or forbidden crops offer tremendous potential to combat malnutrition, poverty and global hidden hunger. Since, overdependence on a few dominant cereal crops viz., rice, maize and wheat is insufficient to meet the global food energy intake; identification, genetic improvement and implementation of various policies for agro-diversification of underutilized crops is highly required. This review enumerates a comprehensive comparative analysis of the nutrient profile of staple crops vs. potent underutilized crops with reference to cultivation constraints, and climate resilience with different agro-diversification strategies. Methodology: Research databases viz. Scopus, JSTOR, Web of Science, EBSCO, Google Scholar, ScienceDirect, PubMed and Academic Search were searched using relevant research queries. Result: Out of 2345 hits, 99 articles pertaining to the subject domain showed that underutilized crops are nutritionally superior, contain health-promoting bioactive components and are climate resilient than cereal crops. However, several constrain hinder the efficient utilization of these crops. Discussion: Despite underutilized crop’s many health benefits, improved cultivation techniques for large-scale production of these crops are still in their infancy, Most of the time, however, scientific knowledge gleaned from various study domains stays within the scientific community. The most crucial need of the hour, therefore, is an efficient network structure connecting governments, farmers, researchers, and businessmen. Moreover, care must be taken to ensure that the policies of governments and INGOs/NGOs are properly implemented within a NUCS framework.